PENGARUH DEBT TO ASSET RATIO (DAR) DAN DEBT TO EQUITY RATIO (DER) TERHADAP RETURN ON ASSET (ROA) PADA PERUSAHAAN PERTAMBANGAN YANG TERDAFTAR DI INDEKS SAHAM SYARIAH INDONESIA PERIODE 2017-2021 - Miftahul Jannah (EKSYA : Jurnal Ekonomi Syariah, 2023)
This research is motivated by the growth of debt which makes return on assets up and down. The purposes of this study are (1) to determine whether or not there is a simultaneous and partial influence of the Debt To Asset Ratio and Debt To Equity Ratio on the return on assets. (2) To determine the unidirectional or opposite relationship of the Debt To Asset Ratio and Debt To Equity Ratio. (3) To find out the most influential variables on return on assets. The sample used in this study was 20 companies from 27 companies which were taken by purposive sampling method in 2017-2021. In this study using quantitative methods and descriptive approaches, by collecting documentation and library data where the data obtained from company documents through the company's official website then carried out various tests such as the classical assumption test to check the health of the data, partial (t) and simultaneous (F) in order to determine the effect or not of the variables used, multiple linear regression test to determine the direction of the influence of variables, determinant coefficients and dominant test in order to determine the dominant variables in influencing return on assets. The results in this study indicate that (1) Debt To Asset Ratio (DAR) and Debt To Equity Ratio (DER) simultaneously and partially have a significant effect on Return On Assets in mining companies listed on the Indonesian Sharia Stock Index (ISSI) for the 2017-2017 period. 2021. (2) Debt To Asset Ratio (DAR) has a negative (opposite direction) effect on return on assets and Debt To Equity Ratio (DER) has a positive (unidirectional) effect on return on assets in mining companies listed on the Indonesian Sharia Stock Index (ISSI). period 2017-2021. (3) Debt to Asset Ratio (DAR) is the most influential of the Debt to Equity Ratio (DER) on Return On Assets in mining companies listed on the Indonesian Sharia Stock Index (ISSI) for the 2017-2021 period. Therefore, the ratio of debt to assets and the ratio of debt to equity, must be considered in developing profitability. Future research is expected to add research variables, samples and increase the research period.